Floral-core terahertz photonic crystal fiber bio-sensor: An exclusive approach to recognizing milk from various animal species - Khalid Sifulla Noor; A.H.M. Iftekharul Ferdous; Most. Momtahina Bani; Md. Golam Sadeque (Applied Food Research)
In this article, an advanced-level type of Photonic Crystal Fiber (PCF) sensor, having a flower shape core with a unique hexagonal cladding, is proposed. Performance for detecting is evaluated in various animal's milk, such as camel, cow, and buffalo milk, with the suggested PCF sensor. The maximum Relative Sensitivities (RS) of the PCF sensor are 88.2 %, 88.5 %, and 88.8 % for detecting camel milk, cow milk, and buffalo milk, respectively. Moreover, it has a negligible Confinement Loss (CL) of 2.04018402 × 10−14 dB/m and Total Loss (TL) of 2.1520000 × 10−01 dB/m and Effective Material Loss (EML) of 0.21520 cm−1. Since Milk is as great source of nutrients such as Calcium, Vitamin D, Vitamin B12, Phosphorus and Protein. The nutrient composition of different animals' milks and their respective quantities are determined by set values at the beginning and differ among the types of milk. As all of them hold the same tone, it becomes challenging to identify them. Our suggested PCF sensor comes with its remarkable detection capacity to identify them. Therefore, the use of suggested PCF sensor will be helpful for both the industry and consumers. For the industry, it aids in ensuring the quality and composition of animal milk. For consumers, it means they can trust that the milk they purchase has been accurately tested and verified for its nutrient content and safety. With the implementation of the PCF sensor, the industry can better ensure the quality and authenticity of animal milk, reducing the risk of fraud and helping consumers make more informed choices about the milk they consume. This contributes to better assurance of proper nutrient intake.